Analisis Kebutuhan Air Bersih dan Pemetaan Potensi Mata Air Wilayah Kecamatan Siotapina Kabupaten Buton - Aswad Asrasal; Slamet Imam Wahyudi; Henny Pratiwi Adi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Clean water demand is a key consideration in planning drinking water supply systems, particularly in areas experiencing population growth and relying on springs as raw-water sources. This study analyzes projected clean water demand through 2035 and maps spring-water potential as a basis for SPAM development in Siotapina District, Buton Regency. A quantitative approach was applied using population data, field surveys conducted in March 2026, spring-discharge measurements using a current meter, and spatial analysis with ArcGIS Pro. Population and water demand were projected using the geometric method, including domestic and non-domestic demand, water losses, maximum-day demand, and peak-hour demand. The population is projected to increase from 17,448 in 2026 to 19,910 in 2035, with peak-hour demand reaching 43.83 L/s. Ten springs were identified with a combined measured discharge of 300.27 L/s. Baahuwu (92 L/s), Waikobi 2 (64 L/s), and Lialamana 1 (57.5 L/s) individually exceed the projected peak-hour demand. The integration of demand projections and spatial information indicates that these springs have strong quantitative potential as primary raw-water sources, while lower-discharge springs may support an integrated supply system. The results provide a quantitative and spatial basis for further technical planning of a sustainable SPAM in Siotapina District.